Statement in regard to the Minister of Health's White Paper on the establishment of "A National Health Service." (1944)
1944 1944 1940s 18 pages HOSPITALS AND WELFARE SERVICES UNION. Statement in regard to the Minister of Health's White Paper on the establishment of "A National Health Service." Government's intention "To establish a comprehensive HEALTH SERVICE for EVERYBODY in this country. They want to ensure that in future every MAN and WOMAN and CHILD can RELY on getting all the advice and treatment and care which they may need in matters of personal health; that what they get shall be the best medical and other facilities available; that their getting these shall not depend on whether they can pay for them, or on any other factor irrelevant to the real need - the real need being to bring the country's FULL RESOURCES to bear on reducing ill-health and promoting good health in all its citizens. GENERAL REVIEW The Government's White Paper on a National Health Service needs special consideration by the members of the Hospitals and Welfare Services Union having regard to its general effect on the Union's membership and also as a National Document. The Paper also needs the most vigilant and critical examination by every Trade Unionist and Citizen. The report in many ways is a most disappointing document failing to outline a COMPREHENSIVE HEALTH SERVICE but mainly concerned in introducing a MEDICAL TREATMENT SERVICE. It has, in our opinion, been prepared without imagination or courage, solely attempting to manacle the medical profession to definite contractual obligations of service in order to control and supervise medical certification for Social Security 'financial benefits'. It is especially disappointing too, as far as the other grades of Health Service Workers (as distinguished from the Medical Workers) are concerned. References to them are very scanty and scattered throughout the document, without slightest element of co-ordination. One important admission by the Minister is worthy of note, and this admission indirectly records a vote of thanks to the representatives of the people, not the Government nor the members of the medical profession. It is the frank admission that our present health services have reached its existing stage by a process of ''evolution" by and through a "long and continous process". This, in our opinion, is a kind of 'back-handed' tribute to those progressive local government authorities who, by their vision and foresight, have endeavoured to create an efficient service in certain localities out of the admitted limitations of existing statutory obligations - and often in face of much opposition, professional and political, departmental or parochial. Whilst this progress has been marked in certain areas - it has been particularly backward in others. It will take more than a ''White Paper" and the luke-warm policy it now enunciates to provide a "levelling" of services, let alone an immediate improvement in the establishment of some uniform and real comprehensive health service worthy of the traditions of this country. The closer one examines the white paper the more one realises that the proposed 'elastic' machinery; the absence of any real democratic control and the curtailment of direct responsibility to the people will make the path of efficient progress 'more slow, and painful'. The Government's intentions are good. The manner in which it is now proposed to implement such intentions are definitely bad, for in every direction the 'professional and political' brake can, and will be applied. What to those engaged at present in the health Services is the great lesson of the White Paper.? It is the need for greater organisation of ALL the Health Workers in one closely knit Trade organisation. It is clear that, in future, there will be an expansion of all the Health Services. This expansion may be gradual, following to a close degree the expansion in the Public Health Services introduced by the operation of the Local Government Act 1929, and the progressive development in certain localities by appropriation under the Public Health Acts. Unorganised and divided the Health Workers will find themselves increasingly at a diadvantage [disadvantage]. 292/847/2/43